Factorial Structure of the Self-Report of Barriers for Practice of Physical Exercise Among Mexican Non Athlete University Students - Ornelas, José René Blanco; Chávez, Juan Francisco Aguirre; Vásquez, Susana Ivonne Aguirre; Pando, Elia Verónica Benavides; García, Perla Jannet Jurado (European Scientific Journal, ESJ, 2018)
The present study intends to investigate if the psychometric results proposed by Niñerola, Capdevila and Pintanel (2006) for the Self-report of Barriers for Practice Physical Exercise (ABPEF) in Mexican university students are replicated. A total of 877 university students (mean age = 20.8 ± 2.5 years) participated. The factorial structure of the questionnaire was analyzed through confirmatory factorial analyzis, which showed that a four factor structure is feasible and adequate. The four factors (body image, fatigue, obligations and environment), according to statistical and substantive criteria, have shown adequate fit indicators of reliability and validity, which correspond to the structure proposed for the original questionnaire. In addition, the results of the factorial analyzis carried out with the subsamples, indicate the existence of strong evidence of the stability of the factorial structure. Further research should replicate these findings in larger samples.